PERAN TRUST, PERCEIVED USEFULNESS, PERCEIVED EASE OF USE, PERCEIVED E-SERVICE QUALITY, DAN PERCEIVED RISK TERHADAP BEHAVIOR INTENTION: SUATU PENELITIAN PADA KIOSK TYME DIGITAL - Nabilla - Nazirwan; Natasha Mannuela Halim; Raihan Fadhil (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2020)
In the era of digitalization and high economic growth, several industries, especially in banking industry, compete each other to give the best innovation in technology information area. Digitalization in banking industry is able to create behavior intention of society to keep using the banking services. This research aims to know the effect of some factors including trust, perceived usefulness, perceived ease of use, perceived e- service quality, and perceived risk in society against to behavior intention in using new technology, where in this context is PT. Bank Commonwealth product, Tyme Digital kiosk.Data collection method used in this research is online questionnaire with sample of 240 respondents who are bank people, having ‘NPWP’, and never using Tyme Digital kiosk. Data analysis is done by using the Structural Equation Modeling (SEM).The summary of the result from this research are: 1) Trust have a positive impact to Behavior Intention. 2) Trust have a positive impact to Behavior Intention. 3) Perceived Usefulness have a positive impact to Behavior Intention. 4) Perceived Ease of Use have a positive impact to Perceived Usefulness. 5) Perceived Ease of Use have a positive impact to Behavior Intention. 6) Perceived e-Service is not proven to have a positive impact to Behavior Intention. (7) Perceived Risk is not proven to have a positive impact to Perceived e-Service Quality. 8) Perceived Risk have a negative impact to BehaviorIntention. Keywords: Trust, Perceived Usefulness, Perceived Ease of Use, Perceived e-Service Quality, Perceived Risk, Behavior Intention.